Photovoltaic systems engineering. - Messenger, Roger A., ....-; Ventre, Jerry, ....- (Boca Raton : CRC, 2004)
Samenvatting:In just the last few years, the increase in worldwide photovoltaic (PV)shipments has grown from 15 to 25 percent per year. Grid-connectedapplications have surpassed stand-alone applications, system componentshave realized significant improvements, and major efforts are underway tobuild a quality control infrastructure for PV systems. Such rapid growthand evolution continues to put engineers skilled in PV systems at apremium.Thoroughly updated, Photovoltaic Systems Engineering, Second Editionoffers a practical engineering basis for PV system design. It providesquick exposure to all system building blocks, then examines both the whysand hows of the electrical, mechanical, economic, and aesthetic aspectsof PV system design-why certain designs are done in certain ways and howthe design process is implemented. Students mastering the contents ofthis book will have the engineering judgement needed to make intelligentdecisions based on a clear understanding of the parameters involved in PVsystems.
Keywords: Zonne-energie elektriciteitsvoorzieningen; Zonnecellen